Mir-23a and mir-125b regulate neural stem/progenitor cell proliferation by targeting Musashi1 - Gioia, Ubaldo (RNA Biol, 2014)
Musashi1 is an RNA binding protein that controls the neural cell fate, being involved in maintaining neural progenitors in their proliferative state. In particular, its downregulation is needed for triggering early neural differentiation programs. In this study, we profiled microRNA expression during the transition from neural progenitors to differentiated astrocytes and underscored 2 upregulated microRNAs, miR-23a and miR-125b, that sinergically act to restrain Musashi1 expression, thus creating a regulatory module controlling neural progenitor proliferation.